Italy : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Italy. (IMF Staff Country Reports; Country Report, 2016)
This 2016 Article IV Consultation highlights that the Italian economy is recovering gradually from a deep and protracted recession. Buoyed by exceptionally accommodative monetary policy, favorable commodity prices, supportive fiscal policy, and improved confidence on the back of the authorities' wide-ranging reform efforts, the economy grew by 0.8 percent in 2015 and continued to expand in the first quarter of 2016. Labor market conditions have been improving gradually, and nonperforming loans appear to be stabilizing at about 18 percent of total loans. Growth is projected to remain just under 1 percent in 2016 and at about 1 percent in 2017.